2020
DOI: 10.3390/ma13092097
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Steel-FRP, FRP and Steel-Reinforced Coral Concrete Beams in Their Flexural Performance

Abstract: In this study, a comparative study of carbon fiber reinforced polymer (CFRP) bar and steel–carbon fiber composite bar (SCFCB) reinforced coral concrete beams was made through a series of experimental tests and theoretical analyses. The flexural capacity, crack development and failure modes of CFRP and SCFCB-reinforced coral concrete were investigated in detail. They were also compared to ordinary steel-reinforced coral concrete beams. The results show that under the same conditions of reinforcement ratios, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Raed et al [ 17 ] believe that the assumption of plane section remain plane in the calculation of deflection of FRP reinforced concrete beams and slabs under high-level load will lead to a significant reduction in the rigidity of FRP reinforced concrete members, resulting in significant deflection. Wang et al [ 18 ] found that the flexural performance of concrete beams of different types of reinforcement is significantly different, and the application of FRP reinforcement to different types of concrete is also different. The existing calculation model is difficult to accurately predict their flexural performance.…”
Section: Introductionmentioning
confidence: 99%
“…Raed et al [ 17 ] believe that the assumption of plane section remain plane in the calculation of deflection of FRP reinforced concrete beams and slabs under high-level load will lead to a significant reduction in the rigidity of FRP reinforced concrete members, resulting in significant deflection. Wang et al [ 18 ] found that the flexural performance of concrete beams of different types of reinforcement is significantly different, and the application of FRP reinforcement to different types of concrete is also different. The existing calculation model is difficult to accurately predict their flexural performance.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the corrosion resistance, FRP bars can be used as a substitute for steel bars in concrete structures. Existing studies have shown that FRP-reinforced CAC beams have a satisfying flexural capacity and deformation capacity, which is comparable to steelreinforced CAC beams (Hu et al, 2017;Li et al, 2016;Wang et al, 2020b). In FRP bar reinforced concrete structures, the interfacial bond strength is of substantial importance to ensure the efficiency of the reinforcing bars.…”
Section: Frp Bar Reinforced Cacmentioning
confidence: 99%
“…Whilst, at ULS, the average crack widths were 4.19 mm and 1.63 mm for under-reinforced and over-reinforced beams, respectively. The experimental results observed that over-reinforced beams with a large number of cracks resulted in low values of crack width [ 17 , 32 , 37 , 38 , 40 , 47 ]. Over-reinforced beams were also recorded to have a slower rate in crack development speed [ 11 , 40 ].…”
Section: Aspect Behavior Of Flexural Strengthmentioning
confidence: 99%